(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This review delves into the effectiveness of folk remedies for treating knee osteoarthritis (KOA), a prevalent degenerative joint disease that significantly impairs quality of life, particularly among the elderly. The piece discusses various risk factors associated with KOA, including age, obesity, diet, and genetic predisposition. It highlights contemporary pharmacological approaches and traditional remedies, particularly those rooted in Chinese and Iranian medical practices. The review emphasizes the role of traditional herbal treatments, moxibustion, and acupuncture, exploring their potential efficacy and safety profiles. It further contextualizes these remedies against the backdrop of increasing concerns regarding the side effects associated with conventional pharmacological approaches, such as NSAIDs and corticosteroids, which can lead to complications over long-term use. Moreover, it addresses the importance of conducting rigorous scientific evaluations of these folk remedies through systematic reviews and controlled trials to establish their effectiveness and inform clinical practice. By balancing the historical use of traditional medicine with modern research methodologies, this paper aims to bridge the gap between folk remedies and contemporary medical practices, offering hope for improved management strategies for knee osteoarthritis patients.